Psychological flexibility and systemic inflammation : cross-sectional and longitudinal associations among Finnish working-age adults with stress and overweight - Kipponen, Tiia (2016)
In search for psychophysiological correlates of psychological flexibility, the purpose of this study was to investigate whether and how psychological flexibility is associated with systemic inflammation. The participants were 132 Finnish working-age adults with psychological distress and overweight or obesity who were taking part in two Acceptance and Commitment Therapy (ACT) - based interventions designed to support lifestyle changes by increasing psychological flexibility. Psychological flexibility was assessed with two self-report questionnaires that measured the general and weight-related psychological flexibility (Acceptance and Action Questionnaire II, AAQ-II; Weight-related Acceptance and Action Questionnaire, AAQ-W). Systemic inflammation was measured with two markers, plasma concentrations of interleukin 1 receptor antagonist (IL-1Ra) and highly sensitive C-reactive protein (hCRP). The assessments were conducted before and after the 8- week intervention and after a 6-month follow-up, at weeks 0, 10 and 36 respectively. Bivariate correlations (Pearson) revealed that the markers of psychological flexibility and systemic inflammation did not correlate with each other on the baseline. Change scores in psychological flexibility correlated inversely with change scores of inflammation markers, AAQ-II with IL-1Ra and AAQ-W with hCRP. An adjusted linear regression modeling indicated that greater improvement in general psychological flexibility during the intervention predicted to a medium extent (r = .27, p = .002) the overall decrease in IL-1Ra from pre- to follow-up measurement. Respectively, greater improvement in weight-related psychological flexibility had a small effect (r = .18, p = .039) on the overall decrease in hCRP from pre- to follow-up measurement. In both interactions, the predictive effect was unidirectional and independent of age, gender, weight (BMI) and psychological symptoms (stress and depression). However, the interaction between AAQ-W and hCRP was intervention specific. To date, this is the first study to examine psychological flexibility in relation to psychophysiology. These preliminary results suggest that improvement in general psychological flexibility (AAQ-II) during an ACT-based intervention had its own single contribution to the overall decrease in inflammation that was independent of confounding effects of psychological symptoms (stress and depression) and weight (BMI). Further research is warranted to confirm these findings and establish the biological basis of psychological flexibility's potential preventive effects on physical health.